AKTUALISASI KAUM MILENIAL MELALUI PEMBELAJARAN DAN PEMBERDAYAAN MASYARAKAT DI DESA KARYA MAKMUR KABUPATEN BANGKA PADA MASA KENORMALAN BARU - Diana Anggraeni; Bob Morison Sigalingging; Dini Wulansari (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2021)
The 2020 Ministry of Research and Technology / BRIN Kuliah Kerja Nyata Pembelajaran dan Pemberdayaan Masyarakat (KKN-PPM) Program located in Karya Makmur Village, Bangka Regency and involving 30 Universitas Bangka Belitung students across study programs aims to provide opportunities for millennials (read: students) UBB to get learning in the field that was not previously obtained in college. This field learning involves the active role of students in knowing problems in society and providing solutions to these problems, which are all summarized in an actualization process. The UBB KKN-PPM program is a Community Service (PkM) activity in the new normal period which runs from July 15 to August 19, 2020. This program divided the group members into seven divisions, namely the UMKM Division, Short Story Division, Dance Division, Taman Bacaan Division, Design Division, Compost Division and Information Technology (IT) Division. The actual output of all divisions that have worked sincerely wholeheartedly while still prioritizing strict health protocols, so that the benefits can be felt by the community, among others: hydroponics, hand sanitization, compost, liquid organic fertilizer, a collection of short stories in three languages, a CD tutorial on traditional Bangka Belitung dance, and the rejuvenation of the village library space accompanied by the Teaching Movement. The actualization of the KKN program was completed and all products were handed over to village officials for follow-up.